Elasto-plastična analiza deformiranja naprave za zaščito pred podletom za motorna vozila - Glavač, Matej (Strojniški vestnik, 2001)
The paper describes a procedure for simulating the elasto-plastic behaviour of a rear-underrun protection device (RUPD), which can be used to estimate whether the design fulfils the ECE R 58 regulation. This regulation prescribes practical device testing, but also allows a computational safety inspection of the protection device. The paper also includes the development of the elasto-plastic computational simulation using the finite-element method that was presented at IAT 99 5. The results of the elasto-plastic analysis simulations load to the conclusion that this method can be used to optimize the RUPD in the design process without the need for practical testing. Computational simulation also reduces the cost of the approval without the need for practical testing. Computational simulation also reduces the cost of the approval procedure.
Keywords: naprave zaščitne; zaščita pred podletom; preskušanje; simuliranje računalniško; simulacija